2018
DOI: 10.1007/s00417-018-3945-5
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the OCT angiographic peripapillary vessel density by ROCK inhibitor ripasudil instillation: a comparison with brimonidine

Abstract: PurposeTo assess the responses of the superficial peripapillary retinal vessel density (VD) and prelaminar flow index (PLFI) to topical Rho-assisted coiled-coil forming protein kinase (ROCK) inhibitor ripasudil and alpha-2 agonist brimonidine using optical coherence tomography angiography.MethodsThis is a prospective, non-randomized, comparative cohort study. We studied the response of optical coherence tomography angiography (OCTA) parameters to drugs in 24 eyes treated with ripasudil and 23 eyes treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 34 publications
1
17
2
Order By: Relevance
“…Some postoperative changes may be confounding. Stopping of glaucoma medications postoperatively may influence retinal perfusion, although published results so far only showed that medications have no change or improved capillary density 49 , 50 . Ocular surface changes may affect the quality of OCTA images, although our signal strength analysis showed that preoperative and postoperative images quality were comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Some postoperative changes may be confounding. Stopping of glaucoma medications postoperatively may influence retinal perfusion, although published results so far only showed that medications have no change or improved capillary density 49 , 50 . Ocular surface changes may affect the quality of OCTA images, although our signal strength analysis showed that preoperative and postoperative images quality were comparable.…”
Section: Discussionmentioning
confidence: 99%
“…However, using animal models, we previously showed that ripasudil is able to reach the retina even with eye drops and that the sufficient retinal concentration of ripasudil was maintained for at least 8 h (34). In addition, Chihara et al (49) reported that ripasudil instillation twice a day enhanced the peripapillary retinal vascular density using OCT angiography. Thus, it will be worthwhile to investigate the effects of anti-VEGF therapy and ripasudil eye drops on rDME in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies considered the efficacy of ROCK. Chihara [5] and Ohta [6] showed that Ripasudil not only lowered IOP but also increased ocular blood flow and the density of peripapillary vessels. Netarsudil and another ROCK, fasudil, enabled an IOP reduction in the range of timolol (slightly less than prostaglandin analogues), which was ongoing for a longer time.…”
Section: New Pharmaceutical Approaches To Treat Glaucoma and New Waysmentioning
confidence: 99%